Enhancing Student Participation and Learning Interest in Social Studies: A Classroom Action Research on the Implementation of Active Learning Methods in Grade V - Ernasari Ernasari; Ester Julinda Simarmata; Rosdiana Samosir (Departement of Mathematics Education, 2024)
This research intends to assess the deployment of active game approaches in social studies learning in class V and its impact on student actions. The research was carried out through a classroom action research approach with two cycles, involving Class V pupils consisting of 24 students. Data was acquired through observation of student activities, analysis of daily test outcomes, and teacher feedback. The results of the investigation demonstrate that the deployment of active gaming approaches offers a positive contribution to student activities. In cycle I, improvements were noted although there were still impediments such as student activity which was not yet optimal. Through reflection in cycle I, changes and adjustments were made in cycle II, which resulted in more significant improvements. The problems experienced, such as low student involvement and a shortage of social studies textbooks, can be solved with help from the school and curricular revisions. Nevertheless, this research presents a good image of the potential of active game methods in improving student engagement and activity in social studies learning. The outcomes of this research can be a reference for teachers and connected parties in establishing creative and responsive learning approaches. Education that is centered towards active student participation can build an exciting and effective learning environment.